Reading Challenges and Strategies Applied in the EFL/ESL Classroom: A Literature Review - Octavia Dwi Hasanah; Dian Fadhilawati; Hamisu Hamisu Haruna (Nexus Publishing, 2026)
This review synthesizes empirical studies published between 2014 -2025 to examine reading comprehension challenges among EFL/ESL learners and the impact of the use of reading strategies the findings reveal that learners face multiple challenges, including limited vocabulary, grammatical difficulties, weak reading process skills, cognitive comprehension issues, psychological and motivational barriers, inadequate instructional support, text complexity, and ineffective strategy use. the review also shows that various reading strategies, such as metacognitive, cognitive, collaborative, technology-supported, guided, and integrated approaches, significantly enhance comprehension, self-regulation, and engagement when implemented through explicit instruction and scaffolded support. However, their effectiveness varies depending on individual differences, including motivation, proficiency level, and cultural background, as well as instructional quality. These findings highlight the importance of developing learner-centered, contextually responsive reading programs that promote autonomy and critical literacy, while future research should examine long-term and differentiated instructional models.